The Role of Perception of Organizational Justice and Employee Commitment on Whistleblowing Intention With Job Satisfaction as an Intervening Variable at PT Maybank Indonesia - KUMALASARI, Nila; NUSANDARI, Arum Wardhani; DEWI, Rusmalia (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to analyze the influence of Perceived Organizational Justice and Organizational Commitment on Whistleblowing Intention, with Job Satisfaction as an intervening variable among employees of PT Maybank Indonesia. A quantitative approach was used in this study, collecting data through an online questionnaire distributed to 45 respondents. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) using the SmartPLS 4 application. The results indicate that perceived organizational justice significantly influences whistleblowing intention, but does not significantly influence job satisfaction. Conversely, organizational commitment significantly influences job satisfaction, but does not directly influence whistleblowing intention. Job satisfaction was shown to act as a partial mediator in the relationship between organizational commitment and whistleblowing intention, but did not mediate the effect of perceived organizational justice on whistleblowing intention. These findings provide important implications for organizations to consider aspects of job satisfaction and commitment in an effort to foster a healthy whistleblowing culture. This study also recommends the development of internal policies and a secure reporting system to increase employee participation in whistleblowing disclosures.